A 17-year time-series of diatom populations‘ flux and composition in the Mauritanian coastal upwelling - Romero, Oscar E.; Ramondenc, Simon (Frontiers in Marine Science, 2022)
Understanding seasonal and multiyear variability of primary producers’ populations in the Mauritanian coastal upwelling system along the northwestern African margin may help to predict future impact of climate change (e.g., nutrient availability, productivity, and phyto- and zooplankton dynamics). For this, continuous, long time-series are required. A major challenge in obtaining these time-series is the logistics associated with the uninterrupted, in-situ sampling over several years. Sediment traps represent a reliable alternative. In this study, we assess the variations of the diatom community in samples almost continuously collected between June 2003 and March 2020 with 17 sediment traps deployed at site CBeu (=Cape Blanc eutrophic), located at c. 20°N-18°45’W, offshore Mauritania in the Canary Current Eastern Boundary Upwelling Ecosystems (CC-EBUE). In addition to describing the multiyear dynamics of the total diatom flux and major shifts in the species-specific composition of the populations, our study addresses questions such as (i) how constant is the intrannual pattern of populations’ occurrence, (ii) what the amplitude of annual changes is, and (iii) how populations’ shifts relate to physical setting dynamics. Matching the occurrence of most intense seasonal upwelling, highest diatom flux maxima mainly occur in spring and summer between 2003 and 2020. The diverse diatom community (e.g., benthic, coastal upwelling, coastal planktonic, and open-ocean diatoms) closely follows the annual cycle of atmospheric and hydrologic conditions. Benthic diatoms dominate during spring and summer (e.g., upwelling season), while open-ocean diatoms contribute the most in fall and winter when the upper water column stratifies. As no persistent –either decreasing or increasing trend of diatom productivity over the 17 sampled years, our results are at odds with Bakun’s hypothesis of upwelling intensification. Anchoring temporal changes of diatoms in a wider environmental frame allows for insights into the complex dynamics of the Mauritanian upwelling ecosystem and the populations’ response to climate forcing. This helps in establishing the scientific basis for modeling future states of the CC-EBUE and/or comparable environments.